Comparação e Análise de Desempenho de Aceleradores Gráficos no Processamento de Matrizes - Gonçalves, Nielsen; Costa, Carlos; Araújo, Josivaldo; Costa, Jessé; Panetta, Jairo (Proceedings of the Workshop on Performance of Computer and Communication Systems (WPerformance), 2015)
In the last years the traditional solutions of High Performance Computing (HPC), such as the insertion or replacement of processors, have undergone major changes with the addition of new features. The use of graphics accelerators have been one of the features by which it has been possible to continue to expand the computational performance. However, as other techniques, this leads to the need for specific programming skills as well that facilitate the extraction of computational power offered by all CPU and GPU set. This paper makes a comparison between technologies like OpenACC, CUDA and OpenMP in performance evaluation for matrix processing.